2021
DOI: 10.3390/healthcare9070883
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of VR Physical Exercise on Cognition in Older Adults with and without Mild Cognitive Decline: A Systematic Review of Randomized Controlled Trials

Abstract: It is well known that physical exercise has beneficial effects on cognitive function in older adults. Recently, several physical exercise programs with virtual reality (VR) have been proposed to support physical exercise benefits. However, it is still unclear whether VR physical exercise (VR-PE) has positive effects on cognitive function in older adults. The purpose of this study was to conduct a systematic review (SR) of the effects of VR-PE on cognitive function in older adults with and without cognitive dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Based on the previous studies [ 23 , 24 , 25 , 26 ], we set the inclusion and exclusion criteria. Randomized controlled trials were included if they met the following inclusion criteria: (1) participants with clinical diagnosis of dementia or cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the previous studies [ 23 , 24 , 25 , 26 ], we set the inclusion and exclusion criteria. Randomized controlled trials were included if they met the following inclusion criteria: (1) participants with clinical diagnosis of dementia or cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang and Kaufman [47], Bleakley et al [48], Ogawa et al [49], Howes et al [50], Stanmore et al [51], Vázquez et al [52], Mansor et al [53], Stojan and Voelcker-Rehage [54], Gallou-Guyot et al [10], Wollesen et al [20], Gavelin et al [19], Sakaki et al [55], Soares et al [56] Reviews…”
Section: Studies Exergames Interventionsmentioning
confidence: 99%
“…One study also showed the effect of VR-based restorative environment on cognitive recovery in individuals with mild-to-moderate depression and anxiety [10]. A recent systematic review revealed beneficial effects on improvement of cognitive performance in older adults with and without mild cognitive decline [15]. Likewise, VR intervention can be useful for cognitive rehabilitation in various clinical conditions.…”
Section: Introductionmentioning
confidence: 99%